Single-center experience of Ex vivo liver resection and autotransplantation for complex hepatic alveolar echinoccosis - Yuan, Jiaqi; Chen, Xiaobin; Hou, Lizhao; Wang, Haijiu; Zhou, Ying; Pang, Mingquan; YangDan, CaiRang; Wang, Zhixin; Fan, Haining (Frontiers in Surgery, 2023)
Objective: To summarize the single-centre experience of Ex vivo Liver Resection and Autotransplantation (ELRA) to treat end-stage hepatic alveolar echinococcosis (HAE). Methods: Retrospective analysis of clinical data and follow-up data of 13 patients admitted to the Affiliated Hospital of Qinghai University from January 2015 to December 1, 2020, with the application of autologous liver transplantation for hepatic alveolar echinococcosis. Result: 13 patients underwent successful total/ semi-ex-vivo liver resection combined with autologous liver transplantation with no intra-operative deaths. Median standard liver volume 1118 (991-1336) ml; median residual liver volume 634 (441-1338) ml; transplanted liver mass 520-1355 g, mean 865.4 g; operation time 9.7-18.5 h, mean 14.15 h; liver-free period 226-365 min, mean 289.23 min. The median intraoperative blood loss was 1900 (300-4000) mL; the median number of erythrocyte suspensions entered was 7.5 (3-20) u. The median length of hospital stay was 32 (9-77) days. 9 postoperative complications occurred, with 7 patients graded at grade III or higher by Clavien-Dindo; 4 patients died postoperatively. 1 patient had recurrent abdominal distension with massive thoracoabdominal fluid and coagulation dysfunction 8 months after surgery and was considered to have small liver syndrome. 1 patient developed HAE recurrence during the follow-up, which was considered intraoperative incisional implantation. Conclusion: ELRA is one of the most valuable therapeutic measures for the treatment of end-stage complicated hepatic alveolar echinococcosis. Precise preoperative assessment of liver function, individualized intraoperative duct reconstruction, and precise management of the postoperative disease can achieve better treatment results.